Impact of Deficit Irrigation on Yield and Fruit Quality of Orange Trees (Citrus Sinensis, L. Osbeck, CV. Meski Maltaise) in Southern Tunisia. (11th December 2017) - Nagaz, K.; El Mokh, F.; Ben Hassen, N.; Masmoudi, M.M.; Ben Mechlia, N.; Baba Sy, M.O.; Belkheiri, O.; Ghiglieri, G.
Abstract: An experiment on deficit irrigation of orange trees ( Citrus sinensis, L. Osbeck, cv. Meski Maltaise) with saline water (1.5 g l ‐1 ) was conducted in the arid region of Medenine, Tunisia. Four irrigation treatments were applied: full irrigation (FI), irrigated at 100% of the crop evapotranspiration; deficit irrigation (DI75) and (DI50), which received respectively 25 and 50% less water than FI; and the farmer's method (FM). Soil water content and salinity were monitored during the orange active period. Yield and fruit quality were measured at harvest and used to analyse water productivity (WP) and net income. Results show a decrease in soil salinity between the spring and winter seasons with maximum values observed for the DI50 treatment. Maximum yield levels were obtained under the FI treatment (26.6 t ha −1 ). Applying continuous deficit irrigation resulted in 24 and 45% yield reduction respectively for DI75 and DI50, compared to FI. Fruit‐quality parameters showed significant differences, with higher levels of total soluble solids for DI50 and better fruit weight for FI and FM. For total water supplies between 415 and 786 mm, WP was in the range 2.9–3.6 kg m ‐3, with the highest values observed for the DI50 treatment and the lowest for FM. The soil water balance‐based irrigation method (FI) generated the greatest net income and the lowest soil salinization. Reduction in water supply produced an equivalent reduction in yield but a much stronger decrease in the economic return: using the DI75 strategy resulted in 25% water saving, 24% reduction in yield and 40% reduction in net income. Copyright © 2020 John Wiley & Sons, Ltd. Résumé: Une expérimentation sur l'irrigation déficitaire de l'oranger ( Citrus sinensis, L. Osbeck, cv. Meski Maltaise) à l'eau salée (1.5 g l ‐1 ) a été réalisée dans la région aride de Medenine, Tunisie. Quatre traitements ont été appliqués: l'irrigation complète (FI) fournissant 100% de l'évapotranspiration, l'irrigation déficitaire (DI75) et (DI50) donnant, respectivement, 25 et 50% moins d'eau que FI, et la méthode de l'agriculteur (FM). La teneur en eau et la salinité du sol ont été mesurées périodiquement au cours de la période active de la culture. Le rendement et la qualité des fruits ont été déterminés à la récolte et utilisés pour analyser la productivité de l'eau et la rentabilité économique des traitements. Les résultats montrent une baisse de la salinité du sol entre le printemps et l'hiver avec des valeurs maximales observées pour DI50. Les rendements maximum ont été obtenus pour le traitement FI (26.6 t ha −1 ). L'application de l'irrigation déficitaire continue a induit une réduction du rendement de 24 et 45% respectivement pour DI75 et DI50 par rapport à FI. L'analyse de la qualité des oranges a montré des différences significatives entre traitements avec des niveaux de sucres totaux solubles plus élevés pour DI50 et des poids moyens de fruits plus élevés chez FI et FM. Pour des apports d'eau entre 415 et 786 mm, la productivité de l'eau s'est située entre 2.9 et 3.6 kg m ‐3 avec les valeurs les plus élevées observées pour DI50 et les plus faibles pour FM. La méthode FI basée sur l'utilisation du bilan hydrique du sol a généré le bénéfice net le plus élevé et provoqué le moins de salinisation du sol. La réduction des apports s'est accompagnée d'une réduction équivalente du rendement et une baisse plus prononcée des revenus. Ainsi, le traitement DI75 a engendré, dans notre cas, une économie d'eau de 25%, une réduction de 24% du rendement et une réduction de 40% des revenus nets. Copyright © 2020 John Wiley & Sons, Ltd.